Subcostal transversus abdominis plane block can improve analgesia after laparoscopic cholecystectomy - Vrsajkov,Vladimir (2018)
Abstract Background and goal of study: After laparoscopic cholecystectomy, patients have moderate pain in the early postoperative period. Some studies shown beneficial effects of subcostal transversus abdominis plane block on reducing this pain. Our goal was to investigate influence of subcostal transversus abdominis plane block on postoperative pain scores and opioid consumption. Materials and methods: We have randomized 76 patients undergoing laparoscopic cholecystectomy to receive either subcostal transversus abdominis plane block (n = 38) or standard postoperative analgesia (n = 38). First group received bilateral ultrasound guided subcostal transversus abdominis plane block with 20 mL of 0.33% bupivacaine per side before operation and tramadol 1 mg.kg−1 IV for pain breakthrough (≥6). Second group received after operation tramadol 1 mg.kg−1/6 h as standard hospital analgesia protocol. Both groups received acetaminophen 1 g/8 h IV and metamizole 2.5 g/12 h. Pain at rest was recorded for each patient using NR scale (0–10) in period of 10 min, 30 min, 2 h, 4 h, 8 h, 12 h and 16 h after the surgery. Results and discussion: We obtained no difference between groups according age, weight, intraoperative fentanyl consumption and duration of surgery. Subcostal transversus abdominis plane block significantly reduced postoperative pain scores compared to standard analgesia in all periods after surgery. Tramadol consumption was significantly lower in the subcostal transversus abdominis plane (24.29 ± 47.54 g) than in the standard analgesia group (270.2 ± 81.9 g) (p = 0.000). Conclusion: Our results show that subcostal transversus abdominis plane block can provide superior postoperative analgesia and reduction in opioid requirements after laparoscopic cholecystectomy.